The Role of Financial Literacy in Moderating the Influence of Fintech and Financial Inclusion on Financial Performance - Khansa Shabihah; Mutamimmah Mutamimmah; Rita Rosalina; Dedi Rusdi; Ahmad Salim (Komunitas Dosen Indonesia, 2025)
Micro, small, and medium-sized businesses (MSMBs) are crucial for boosting community economic empowerment and job creation. Unfortunately, many players in the MSME sector struggle with good financial management due to even a simple lack of knowledge about financial reporting. In this study, we aim to analyze how fintech and financial inclusion affect the financial performance of micro, small, and medium-sized enterprises (MSMEs), controlling for financial literacy as a moderating variable. A quantitative explanatory research approach is utilized in this work. Using a purposive sample technique, one hundred MSME players in the culinary sector of Semarang City were chosen. The data was collected via secondary sources, surveys, and interviews conducted by the Central Java Provincial Cooperatives and MSMEs Office. Moderated Regression Analysis (MRA) and multiple linear regression were employed for the data analysis. The findings were reliable according to the traditional premise. Financial inclusion (β = 0.171; p < 0.05) and financial performance (B = 0.289; p < 0.05) were both markedly enhanced by fintech, according to the study's findings. The effect of financial literacy on financial success was stronger than that of fintech (B = 0.017; p < 0.05) and financial inclusion (B = 0.022; p < 0.05). This research highlights the critical importance of financial literacy for MSMEs to maximize digital financial services.